Pengaruh Masa Kerja dan Kepuasan Kerja terhadap Komitmen Organisasi Guru Honor (Studi Kasus pada SMA Unggulan di Kota Palembang) - Maya Yusnita (Holistic Journal of Management Research, 2015)
This study investigated the influences of job tenure and job satisfaction to organizational commitment of several part-time teachers. Participants were 50 (male = 24, female = 26), selected from the best four of senior high schools in Palembang. Multiple regression was used to analyse the data collected. Results showed that job tenure and job satisfaction significantly predicted organizational commitment.